2019
DOI: 10.1105/tpc.19.00081
|View full text |Cite
|
Sign up to set email alerts
|

Separating Golgi Proteins from Cis to Trans Reveals Underlying Properties of Cisternal Localization

Abstract: The order of enzymatic activity across Golgi cisternae is essential for complex molecule biosynthesis. However, an inability to separate Golgi cisternae has meant that the cisternal distribution of most resident proteins, and their underlying localization mechanisms, are unknown. Here, we exploit differences in surface charge of intact cisternae to perform separation of early to late Golgi subcompartments. We determine protein and glycan abundance profiles across the Golgi; over 390 resident proteins are ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 102 publications
(136 reference statements)
3
46
0
Order By: Relevance
“…Analyses of the signal peptide (SP) and transmembrane (TM) span sequence properties were performed as previously described ( Parsons et al., 2019 ) with only minor modifications. SP-containing proteins and monotopic integral membrane proteins were identified using SignalP 4.1 ( Nielsen, 2017 ) and TMHMM 2.0 as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Analyses of the signal peptide (SP) and transmembrane (TM) span sequence properties were performed as previously described ( Parsons et al., 2019 ) with only minor modifications. SP-containing proteins and monotopic integral membrane proteins were identified using SignalP 4.1 ( Nielsen, 2017 ) and TMHMM 2.0 as described above.…”
Section: Methodsmentioning
confidence: 99%
“…The overlap with SYP32-mCherry was higher than that with SYP43-mCherry, indicating a slight enrichment in the cis- Golgi (Fig 2b and 2c). In further support of the Golgi localisation, both Arabidopsis GH43s were identified in Golgi-enriched cell extracts in global proteomics experiments (Parsons et al, 2012; Parsons et al, 2019).…”
Section: Resultsmentioning
confidence: 65%
“…While N-glycosylation begins in the endoplasmatic reticulum (ER) as co-translational en bloc transfer of a preformed oligosaccharide that is subsequently modified in the Golgi, type II AG biosynthesis is entirely Golgi-localized and depends on the hydroxylation of specific prolyl residues in the cis-Golgi followed by galactosylation of isolated Hyp residues and sequential build-up of type II AG in subsequent Golgi compartments. In a recent proteomics study, several P4H isoforms were found the cis and medial Golgi compartment, while HPGT2 was localized in the medial Golgi (Parsons et al, 2019). Some type II AG biosynthetic enzymes such as AtGALT31A have also been colocalized with exocyst protein Exo70E2 in a novel compartment, a finding whose significance remains to be investigated (Poulsen et al, 2014).…”
Section: Molecular Biology Of Type II Arabinogalactan Biosynthesismentioning
confidence: 97%